MANAJEMEN KRISIS DIVISI HUBUNGAN PEMERINTAH DAN MASYARAKAT (HUPMAS) DALAM MEMPERTAHANKAN CITRA PT. PERTAMINA UNIT PENGOLAHAN II DUMAI - Ellyzabet Sihol Marito; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Crisis can be minimized with good crisis management from company management. Crisis management is one aspect that must be prepared and owned by the company to face a crisis that is usually unexpected or sudden, such as the crisis experienced by PT. Pertamina RU II Dumai is the company's exploding refinery that also disturbs the community and repeated and unpredictable since 2001, 2009, 2014 and 2017. Crisis management will succeed if supported by a good strategy from the company so that can maintain the company’s image. Therefore, the purpose of this study is to determine the steps of crisis management and crisis management strategies undertaken division Hupmas PT. Pertamina Refinery Unit II Dumai.The research method used is descriptive qualitative research. Data collection techniques used are in-depth interview techniques and documentation with six informants selected using purposive techniques. In this study the researcher uses grounded research methods or Miles and Huberman models for data analysis that is through the data reduction flow, data presentation and conclusion. To test the validity of the data obtained, the researchers used the triangulation technique.The results of this research Hupmas crisis management PT. Pertamina Refinery Unit II Dumai has been good through five steps: identification, analysis, isolation, choosing strategy and implementation of crisis control and responsible to society through ongoing social responsibility. The step is supported by the existing strategy is to determine the potential crisis of the company that is refineries that can not function properly; identify affected audiences ie companies, communities, and local governments; as well as having the procedure followed.Keywords: PT. Pertamina RU II Dumai, Crisis Management, Maintain Image